INTERPRETASI HASIL KADAR SGOT DAN SGPT PENDERITA HEPATITIS B DI RUMAH SAKIT KHUSUS BEDAH HASTA HUSADA MALANG: INTERPRETATION OF SGOT AND SGPT LEVELS OF HEPATITIS B PATIENTS AT HASTA HUSADA SPECIAL SURGERY HOSPITAL MALANG - Nugroho, Faisal Agung; Watoyani, Tonny; Santoso, Setyo Dwi (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2025)
Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) are enzymes produced in high levels in blood serum when liver cells are severely damaged. Liver cell damage may occur due to an immune response to the Hepatitis B virus. Hepatitis B virus (HBV) is a virus that can cause an inflammation of the liver. SGOT and SGPT levels in HbsAG reactive patients can show varying levels depending on the severity of the infection and the patient's immune response. This study aimed to identify SGOT and SGPT levels in hepatitis B patients The study was conducted with a descriptive observation design. The population of hepatitis B patients were 30 people. The sampling technique was accidental sampling. The results of the SGOT study in Hepatitis B patients were 16.6% of patients had normal SGOT levels, while 83.4% of patients had elevated SGOT levels. Similarly, 5 patients (16.6%) had normal SGPT levels, and 25 patients (83.4%) had elevated SGPT levels. Among the patients, 30% were female and 70% were male. Based on age, 30% were adults, and 70% were elderly. This research can be concluded that most patients with Hepatitis B had high SGOT and SGPT levels.